Pengaruh Green Banking Disclosure Terhadap Nilai Perusahaan Pada Bank Umum Syariah Di Indonesia - Wahid Wachyu Adi Winarto; Tri Nurhidayah; Sukirno Sukirno (Department of Islamic Banking, Faculty of Islamic Economics and Business, UIN K.H. Abdurrahman Wahid Pekalongan, 2021)
This study aims to analyze the effect of Green Banking Disclosure on firm value. The method used is quantitative by conducting content analysis on Green Banking Disclosure items based on the Green Banking Disclosure Index developed by Bose, Khan, Rashid, & Islam (2018). Firm value is measured using the Tobins'q ratio. Regression analysis technique is used in performing statistical tests. The population in this study are all Islamic commercial banks registered with the Financial Services Authority that have been listed on the Indonesia Stock Exchange during 2017 to 2020 by providing criteria for the samples taken. The results showed that there was a significant positive effect of Green Banking Disclosure on firm value in Islamic banking.